Direct power control and back-stepping-based direct power control for dual-stator brushless doubly-fed wind power generator - Xiaoying Su; Liancheng Zhu; Fengge Zhang (PLoS ONE, 2025)
This paper proposes a novel-structured Lyapunov-based back-stepping direct power control (BS-DPC) for an emerging dual-stator brushless doubly-fed wind power generator (DSBDFWPG). The DSBDFWPG features two coaxial stators (inner/outer) and a specially designed cage-barrier rotor separated by a non-magnetic ring, maximizing the internal space utilization of large-scale wind turbines to enhance power and torque density. The inner/outer power/control windings couple with corresponding rotor sections, respectively. Unlike traditional look-up table DPC (LUT-DPC) or generic nonlinear methods, the proposed BS-DPC is rooted in Lyapunov stability theory, ensures global asymptotic stability, while synergizing with SVPWM technology to suppress power fluctuations, reduce current THD, and enhance reliability/robustness. Comprehensive simulations and experiments conducted on a 50 kW DSBDFWPG prototype (12/8 poles) validate BS-DPC’s superiority overwhelming LUT-DPC in achieving variable speed constant frequency operation, maximum power point tracking, reactive power/unit power factor control, and harmonic distortion mitigation.